The Impact of the European Union’s Palm Oil Resolution Policy on the Indonesian Economy Sector - Fatima Benyaich; Hendra Maujana Saragih; Joel Jeremis Siburian (Yayasan Ilomata, 2023)
Indonesia as the world's largest producer and consumer of palm oil is experiencing considerable challenges due to the enactment of the The European Union (EU) Parliament Resolution on the use of palm oil and on overcoming the issue of deforestation. The Union issued a RED policy aiming at directing the European community to use energy-efficient and emission-free fuels. The regulation comprises a rejection of palm oil and its derivative products. The ban on importing such products imposed by the European Union has caused a decrease in Indonesia's GDP by 1155.28 million Euros. In addition, this impacted the employment sector, particularly the oil palm farmers who experience a decrease in income. Despite the issuance of the European Union policy that prohibit or restrict palm oil import, the EU has dependence on Indonesia’s palm oil since they can not produce the oils on a large scale in order to meet their needs. This is a qualitative study and the data collection technique is the heritage study methods obtained from journal, scientific journals on similar topics. As for the theoretical analyses, the mercantilism approach with the aim to use economic policies to maximize the state’s wealth as a means of political power is implemented.